Students’Perception And Practices of Using Tiktok for Learning Speaking Skills in Efl University Contexts - Zumrotul Aulia; Fera Zasrianita; Andriadi Andriadi (The Future of Education Journal, 2026)
This study aimed to investigate students’ perceptions, independent practice strategies, and speaking performance through the utilization of TikTok in an EFL context. This research employed a mixed-methods design involving 38 secondary school students as the primary participants. Data were gathered through a comprehensive collection process utilizing student questionnaires, speaking proficiency tests (short monologue activities), and individual semi-structured interviews. The quantitative results from the questionnaire revealed that the utilization of TikTok was highly valued by the students, where the perceived benefits in enriching vocabulary and pronunciation achieved the highest score at 78%, followed by its convenience for independent practice (72%) and high learning engagement (73%). Furthermore, the students' actual speaking performance in the short monologue activity was categorized as "Good," as evidenced by a cumulative average score of 76%, with the clarity of message achieving the highest criterion at 84%. However, the qualitative interview data highlighted a significant gap between passive digital content consumption and active language production. Almost all students admitted they had never attempted to create or upload their own speaking content on TikTok due to deep-seated affective barriers, specifically high speaking anxiety, shyness, and a fear of public digital judgment. In conclusion, while TikTok serves as a highly effective tool for autonomous linguistic input and independent repetition (shadowing), technology-enhanced autonomous learning must be combined with structured, low-anxiety classroom environments to effectively translate students' receptive knowledge into active and confident oral communication.